TINJAUAN PENGARUH PENAMBAHAN SERAT POLYPROPYLENE DAN PEMANFAATAN BETON ULTRA HIGH PERFORMANCE TERHADAP KETAHANAN ABRASI BETON - Hidayat, Maulana Nur; Solikin, Mochamad; Harnaeni, Senja Rum (Politeknik Negeri Semarang, 2025)
Concrete is a material that is widely used in the construction process, proven in various sectors widely used such as foundation construction, building structures, road pavements and water channels. However, concrete still has many weaknesses in abrasion resistance. To improve the quality of concrete abrasion resistance, the addition of Polypropylene fibers and the use of Ultra High Performance Concrete (UHPC) can be used. The fibers used in the study used Polypropylene fibers and the compressive strength of concrete with the UHPC method was planned to be more than 80 MPa. Mix planning was carried out using the American Concrete Institute (ACI) method with adjustments from trial and error. Furthermore, testing was carried out and test data was obtained which will be continued with the analysis and discussion process to draw conclusions. This study is intended to test the abrasion resistance of UHPC concrete with the addition of 0.2, 0.4, 0.6 polypropylene fibers, with the pressurized water spray method at the age of 28 days. The test results showed 0.351%, 0.284%, 0.369%.